Evaluasi Sistem Administrasi Pengelolaan Mahasiswa Penerima Beasiswa Pemuda Tangguh Dinas Kebudayaan Kepemudaan dan Olahraga serta Pariwisata Kota Surabaya Menggunakan Metode CIPP - Devy Novyana; Meylia Elizabeth Ranu (JURNAL ADMINISTRASI KANTOR, 2025)
Abstract: One of the scholarship programs offered by the Surabaya City Government to students who live in Surabaya City and meet the necessary requirements is the Surabaya Resilient Youth Scholarship. The purpose of this study is to use the CIPP (context, input, process, product) evaluation method to assess the administrative management of the implementation of the Surabaya Resilient Youth Scholarship program. This research used qualitative methodology with data collection techniques of observation, interview, and documentation study. Based on the study findings, the management of the Surabaya Resilient Youth Scholarship program has been implemented in a manner that meets the four criteria of the CIPP evaluation technique (context, input, process, and product). The findings of this evaluation suggest that the program should be maintained with minor adjustments to the timeliness of the Surabaya Resilient Youth Scholarship funding. Keywords: Surabaya Resilient Youth Scholarship Program, Evaluation, CIPP